WEB-BASED INFORMATION SYSTEM FOR ELECTION OF OSIS CHAIRMAN OF YAPIM TARUNA MARELAN VOCATIONAL SCHOOL - Ega Fitra Permana (Penelitian dan Pengembangan Ilmu, 2024)
YAPIM TARUNA MARELAN VOCATIONAL SCHOOL is a private school located in Marelan Pasar IV, where in every election for chairman and deputy chairman of the OSIS, so far they still use a manual system. The use of paper as a medium for conveying the vision and mission and valid ballot papers, problems are often encountered in the process, both When writing the candidate's name or number, the paper is wet, the paper is torn and so on, this causes the calculation process to be hampered and the calculation results to be inaccurate. With the e-voting system, the election process becomes easier and does not take a long time so it does not interfere with the learning process. Apart from that, the calculation process also becomes easier and faster.